Neck dose-limiting rings reduce head and neck lymphedema in early nasopharyngeal carcinoma patients undergoing IMRT: a dosimetric-clinical validation - Kai Liao; Yunhong Tian; Huijun Li; Ronghui Zheng (Scientific Reports)
Abstract This study aimed to determine the optimal limiting dose to reduce head and neck lymphedema in patients with early nasopharyngeal carcinoma (NPC) receiving intensity-modulated radiotherapy (IMRT) by setting dose limiting rings at the anterior and posterior regions of the neck. A total of 15 patients with early NPC were included, and 5 sets of IMRT plans were designed for each patient. Plan A was a conventional plan without dose limiting rings, while Plans B-E were set dose limiting rings with gradients of 20 Gy, 18 Gy, 16 Gy, and 14 Gy, respectively, whose remaining parameters were consistent with Plan A. Through Analysis of Variance (ANOVA) for randomized block design data and Bonferroni pairwise multiple comparisons, the impact of dose limiting rings on target coverage and doses to organs at risk was evaluated and the optimal limiting dose was determined. After that, 50 patients with early NPC (25 with rings according to the optimal limiting dose, 25 without rings) were treated with IMRT to determine if there was a difference in the incidence of head and neck lymphedema. Ultimately, 16 Gy was determined as the optimal limiting dose threshold for achieving the balance of target coverage and protection of organs at risk. Compared with the conventional plan, setting cervical anterior and posterior dose limiting rings of 16 Gy did not affect the target dose coverage (all P > 0.05), only slightly affected homogeneity index and increased monitor units (MUs) (both P < 0.05). The doses of the inner ears, mandible, and brainstem were not affected (all P > 0.05), meanwhile, the doses of the oral cavity, larynx, and thyroid were reduced significantly (all P < 0.05). The doses of the parotid glands and spinal cord slightly increased (both P < 0.05), but still within the tolerance range. Clinical cohort verification showed that setting the dose limiting rings of 16 Gy at the anterior and posterior regions of the neck significantly reduced the occurrence of head and neck lymphedema (P < 0.05). Through dosimetric and clinical cohort verification studies, the optimal limiting dose for the cervical anterior and posterior dose limiting rings has been determined, hoping to provide a new design method of IMRT plans to reduce head and neck lymphedema after radiotherapy for early NPC.